Epigenetics and Disease Pharmaceutical Opportunities - Gasser, Susan M.; Li, En.; SpringerLink (Online service) (Basel : Springer Basel : Imprint: Springer, 2011)
Epigenetics has emerged recently as an important area of molecular biological studies. Epigenetic modifications lead to potentially heritable but reversible alterations in the expression of genes that determine cell fate. Epigenetic misregulation is thus often linked to degenerative diseases, cancer and neuronal disorders. Recent biomedical interest in this regulatory system stems from the fact that epigenetic, in contrast to genetic, alterations are in principle amenable to pharmacological intervention. A few epigenetically active drugs, for example histone deacetylase inhibitors (HDACi) and DNA methyltransferase (DNMT) inhibitors, have been approved by FDA for treatment of cancers such as CTCL, MDS, and AML. This volume explores the scientific background for clinical applications of epigenetically active drugs. Included are descriptions of epigenetic controls over gene expression, the post-transcriptional silencing of genes by RNA interference (RNAi) and microRNAs, as well as new findings from stem cell research which are relevant to pharmacological applications.
DNA Methylation and Cancer -- Genome-wide Epigenetic Modifications in Cancer -- DNA Repair and the Control of DNA Methylation -- Errors in Erasure: Links Between Histone lysine Methylation Removal and Disease -- Histone Modifications in Cancer Biology and Prognosis -- Dynamics of Histone Lysine Methylation: Structures of Methyl Writers and Eraser -- Epigenetic Mechanisms of Mental Retardation -- Histone and DNA Modifications in Mental Retardation -- HDAC Inhibitors and Cancer Therapy -- Epigenetic Mechanisms in Acute Myeloid Leukemia -- The Liver-Specific MicroRNA miR-122: Biology and Therapeutic Potential -- Witold Filipowicz and Helge Großhans -- Transcriptional Regulatory Networks in Embryonic Stem Cells -- Small Molecules in Cellular Reprogramming and Differentiation.
Keywords: Medicine; Medical genetics; Biomedicine; Gene Function